Phylogenetic diversity of Archaea in the intestinal tract of termites from different lineages. (24th February 2015) - Shi, Yu; Huang, Zhou; Han, Shuai; Fan, Shuo; Yang, Hong
<x xml:space="preserve">Abstract</x> Termites are among the few arthropods that emit methane to the atmosphere, which is a significant source of global greenhouse gas due to their huge biomass on earth. In this study, phylogenetic diversity of Archaea of five termite species from different lineages were analyzed based on 16S rRNA genes. Archaea associated with wood‐feeding lower termite, R. chinensis were exclusively Methanobrevibacter in the order Methanobacteriales. This type of methanogens was also found in Nasutitermes sp. and Microcerotermes sp. but not in the fungus‐cultivating termites, Odontotermes formosanus and Macrotermes barneyi, which harbor Archaea of the order Methanoplasmatales and Methanosarcinales in their guts. Archaeal diversity of wood‐feeding higher termites was higher than wood‐feeding lower termites. The highest archaeal diversity was found in Nasutitermes sp. In addition to methanogens affiliated with the orders Methanobacteriales, Methanomicrobiales, and Methanoplasmatales, 37% of archaeal clones were affiliated with non‐methanogenic Thaumarchaeota. The results of this study will be significant for further understanding of symbiotic relationship between intestinal microbiota and termites.